Antigen processing and presentation: modulation by innate immune signals - Watts, Colin (Henry Stewart Talks, 2009)
Conventional and non-conventional antigen processing pathways, Innate stimuli boost antigen capture, processing and presentation, Destructive antigen processing is minimised in dendritic cells (DC), Class II MHC display is regulated by ubiquitination, Linking antigens and TLR ligands can enhance presentation, Distinct endocytic compartments and/or distinct dendritic cell sub-sets may host antigen presentation on class I MHC molecules (cross-presentation) and on class II MHC molecules, Antigen bearing migratory DC and lymph node resident DC can collaborate to induce T cell responses
Archived at 2016/06/22